Stratospheric"Cist"and Water Vapor Budget in the Stratosphere - Iwasaka, Yasunobu (1981)
P(論文) The growth condition of ice crystal particles in the winter season of the polar stratosphere is discussed. Numerical calculation supports the idea that the formation of ice crystal particles in the polar stratosphere (stratospheric "Cist" cloud particles) can affect the stratospheric water vapor budget on a global scale. departmental bulletin paper